Imaging early endothelial inflammation following stroke by core shell silica superparamagnetic glyconanoparticles that target selectin - Farr, Tracy D.; Lai, Chian-Hui; Grünstein, Dan; Orts-Gil, Guillermo; Wang, Cheng-Chung; Boehm-Sturm, Philipp; Seeberger, Peter H.; Harms, Christoph (American Chemical Society, 2014)
Activation of the endothelium is a pivotal first step for leukocyte migration into the diseased brain. Consequently, imaging this activation process is highly desirable. We synthesized carbohydrate-functionalized magnetic nanoparticles that bind specifically to the endothelial transmembrane inflammatory proteins E and P selectin. Magnetic resonance imaging revealed that the targeted nanoparticles accumulated in the brain vasculature following acute administration into a clinically relevant animal model of stroke, though increases in selectin expression were observed in both brain hemispheres. Nonfunctionalized naked particles also appear to be a plausible agent to target the ischemic vasculature. The importance of these findings is discussed regarding the potential for translation into the clinic.